2014
DOI: 10.1007/s00401-014-1269-z
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 is a key player in the clinical features associated with Alzheimer’s disease

Abstract: The aim of this study was to determine whether the TAR DNA-binding protein of 43kDa (TDP-43) independently has any effect on the clinical and neuroimaging features typically ascribed to Alzheimer’s disease (AD) pathology, and whether TDP-43 pathology could help shed light on the phenomenon of resilient cognition in AD. Three-hundred forty-two subjects pathologically diagnosed with AD were screened for the presence, burden and distribution of TDP-43. All had been classified as cognitively impaired or normal, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
402
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(439 citation statements)
references
References 46 publications
33
402
3
1
Order By: Relevance
“…5D) and previously by Qin et al [22]. Importantly, we found that both the DNA oligos (TT) 6 and (TG) 6 …”
supporting
confidence: 85%
See 1 more Smart Citation
“…5D) and previously by Qin et al [22]. Importantly, we found that both the DNA oligos (TT) 6 and (TG) 6 …”
supporting
confidence: 85%
“…Nine years ago, TDP-43 was found to form aberrant polyubiquitinated, hyperphosphorylated cytosolic aggregates that have been causatively linked to amyotrophic lateral sclerosis/ frontotemporal lobar degeneration (ALS/FTLD) [4,5] and, more recently, to Alzheimer's disease [6]. The protein contains an N-terminal domain (NTD), two RNA recognition motif (RRM) RNA-binding domains and a long, intrinsically disordered C-terminal region.…”
mentioning
confidence: 99%
“…Noteworthy, TDP43-pathology has been reported to be relatively common in AD [4][5][6][7][8][9][10][11][12][13][14] and in line with this, TDP43-pathology was observed in as many as 88% of our cases with severe AD related pathology (Braak stages V-VI). It should be noted that clinical studies reporting that EP is common in AD include all subjects with AD diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…In AD, the hippocampal formation displays substantial pathology including AD related hallmark lesions such as neurofibrillary tangles and neuritic plaques [3]. Furthermore, many reports have indicated that a substantial number of AD subjects, in addition to the AD related lesions, also display TAR DNA binding protein 43 (TDP43) within the hippocampus [4][5][6][7][8][9][10][11][12][13][14]. TDP43 related pathology is primarily seen in subjects with frontotemporal lobar degeneration (FTLD) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additional data are required to further characterize the existing tau radioligands, including quantitative validation toward full kinetic modeling, test-retest studies, and human dosimetry. Ultimately, neuropathologic correlations with PET imaging findings will be necessary to confirm tau selectivity against colocalized key proteins besides Ab, such as a-synuclein and TDP-43 (21). Head-to-head studies will allow direct comparisons between radiotracers.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%